IMPLEMENTASI PROGRAM REVITALISASI BAHASA DAERAH OLEH KANTOR BAHASA PROVINSI KALIMANTAN TIMUR: Studi pada Bahasa Kenyah di Desa Pampang Kota Samarinda - Ghazlina, Sonya Soraya; Rande, Santi; Kusuma, Aji Ratna; Apriani, Fajar (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to determine the implementation of the Kenyah Language Revitalization Program by the East Kalimantan Provincial Language Office in Pampang Village, Samarinda City, and its inhibiting factors. This research uses a descriptive type with qualitative methods, with primary data sources through interviews with key informants of the Kenyah Language Revitalization Coordinator of the East Kalimantan Provincial Language Office. Secondary data sources include press release information, documents, and archives related to the revitalization program. Data collection techniques include observation, interviews, and documentation. The data analysis used was an interactive model analysis developed by Miles, Huberman and Saldana. The implementation of the Kenyah Language revitalization program in Pampang Village was successfully carried out by the East Kalimantan Provincial Language Office as the implementor. This is evident from the six stages of the regional language revitalization program from the 17th episode of the Merdeka Belajar curriculum that have achieved their goals. Starting from the coordination meeting stage, group discussions, teacher training, transmission to the Provincial Mother Language Bud Festival were successfully realized in the revitalization of Kenyah language in Pampang Village. However, during the process it turned out that there were obstacles that caused each stage not to be maximized perfectly, namely: 1) not maximizing the implementation of Samarinda Mayor Regulation Number 15 of 2022 which does not have specific policy derivatives related to local content-based revitalization and 2) community-based revitalization modules that cannot be applied in Pampang Village schools due to the absence of local content of Kenyah Language in the school.